Agriculture negotiations in the WTO (New Delhi, 2009)
The agriculture sector had effectively been kept out of the multilateral trading system established through the GATT in 1947. This anomaly was rectified during the Uruguay Round negotiations, culminating in the formation of WTO in 1995, when multilateral disciplines were introduced in the agricultural sector. This agreement is a significant step towards building fairer competition and distortion free regime for trade in agricultural goods. The WTO Agreement on Agriculture (AoA) seeks to improve market access and to reduce trade distorting subsidies in agriculture products. In the ongoing Doha Round of negotiations, the effort is to further liberalise agriculture trade and to further discipline the trade distortion. Agriculture negotiations are of critical importance to India as two-thirds of its population depends upon agriculture, a large number of which includes small and marginal farmers. In these negotiations, India has been arguing for the introduction of a regime which provides adequate protection to its domestic sensitivities in the agriculture sector. At the same time, India is also seeking greater market access for its products in developed countries by disciplining and capping their trade distorting subsidies.
Keywords: Agreement on agriculture